The influence of education level, occupation, income and age in choosing mutual funds as instruments of investment - Siska Wulandari; Rina Nurjannah (Institute of Computer Science (IOCS), 2023)
Investment activities are not apart from how we are able to process our resources and funds to be able to develop our capital, the Reksa Fund is one type of investment and is a container used to collect funds from the funding society to be invested in a portfolio of effects by the investment manager. In its development, investment requires income, level of education, age maturity and job certainty can influence the decision to choose investment interest in investment instruments. This research is a quantitative study with a descriptive format, processing primary data from a questionnaire with a Likert scale. The population involved in this study is the Millennial Generation. Research findings show that education, employment, income, and age have a significant influence on millennial generation decisions in choosing money as an investment instrument. High level of education, stable, high-income jobs, and older age tend to prefer equity as a more promising and low-risk investment instrument.